Does it pay for firms? Costs and benefits of the SkillsFuture Earn and Learn Programme in Singapore - Ursula Renold; Thomas Bolli; Stefan C. Wolter (ETH Zurich, KOF Swiss Economic Institute, 2018)
The SkillsFuture Earn and Learn Programme (ELP) targets graduates from the Institute of Technical Education (ITE) and Polytechnics. During the programme's 12-to-18-month duration, ELP participants spend about 20% of their time in classroom education at the ITE and Polytechnics and 80% in structured workplace training. In order to introduce the programme in 2015, participation of both students and firms was subsidized. This raises the question of whether these subsidies are necessary in the long run, so this research project aims to measure the costs and benefits of the ELP from the perspective of firms. The methodology uses a mixed-method design that combines quantitative surveys of both participating and non-participating firms with qualitative interviews among firms that participate in the ELP.
Keywords: 330